Meanings and practices of learning from incidents: a social constructivist perspective of incident reporting systems. Issue 4 (21st April 2017) - Rossignol, Nicolas; Hommels, Anique
ABSTRACT: Incident reporting systems (IRSs) are used in many organisations as tools that promote safety by allowing to collectively learn from incidents. In this paper, we propose a social constructivist approach to learning from incidents, in which the focus is not purely on safety, but on the technology of incident reporting itself. We employ Wiebe Bijker's work on the Social Construction of Technology to open up the analysis of a specific IRS in use at the Belgian Nuclear Research Center. For this purpose, we carried out 28 interviews with key local actors and collected documents and observation notes. Such social constructivist perspective provides detailed insight into the practices of reporting and the meanings of learning from incidents. Our research shows that various actors within the organisation frame the IRS differently. These framings each have their own implications for the vulnerability of the organisation.